Microstructure and mechanical properties of C/C composite/Ti6Al4V joints with a Cu/TiCuZrNi composite brazing alloy. Issue 5 (April 2016) - Song, Xinrui; Li, Hejun; Casalegno, Valentina; Salvo, Milena; Ferraris, Monica; Zeng, Xierong
Abstract: C/C composites and Ti6 Al4 V sheets were joined using a novel Cu/TiCuZrNi composite braze and the effect of Cu foil thickness on the microstructure and mechanical properties of the joints were investigated. A composite joining material, consisting of a TiC particle reinforced brazing alloy formed in situ during the brazing process was obtained. Before the joining process, the C/C composite surface was modified by solid state reaction with chromium to form a chromium carbide coating. This carbide reaction layer can react with the Ti-based brazing alloy and form evenly distributed TiC particles. The maximum apparent shear strength of as-received joint was 39±8.5 MPa obtained by using a 40 μm thick Cu foil together with the TiCuZrNi alloy; this value was 70% higher than the mechanical strength obtained for joints brazed with the TiCuZrNi alloy only.